Analisis Determinan Pengeluaran Konsumsi Rumah Tangga di Thailand - Nadia Veni Karina; Muhammad Sri Wahyudi Suliswanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Consumption plays an important role in a country's economic growth, making it the main focus of the government in designing economic policies. This study aims to analyze the factors that affect household consumption in Thailand. The research method used is Ordinary Least Square (OLS) to evaluate the impact of these variables on consumption. The results of the analysis show that Gross Domestic Product per capita, population, and consumption credit have a significant positive influence on household consumption in Thailand. On the other hand, interest rate has a negative, albeit insignificant, influence on household consumption. These findings provide important insights for policymakers in regulating the economic factors that influence household consumption behavior. By understanding these factors, the Thai government can design more effective policies to promote economic growth through stimulating household consumption. Keywords: HFCE, GDP Percapita, Population, Interest Rate, Consumption credit